Evaluation of the potential of matoa (Pometia pinnata) leaf extract as an antioxidant activity in pasteurized milk - Ratmawati Malaka; Munirah; Fatma Maruddin; Maynor Alberto Vargas Vargas; A Jimpenez Silva (jurnal1, 2023)
The research objective was to study the influence of the addition of matoa (Pometia pinnata) leaf extract (MLE) and various pasteurization methods (PM) on the antioxidant activity (AA) and physicochemical characteristics of pasteurized milk (PMi). The MLE was added at the level of 0%, 0.05%, 0.10%, 0.15%, and 0.20% into milk and pasteurized to low temperature for long-time pasteurization (LTLT) (63°C for 30 min) or a high-temperature short time (HTST) (72°C for 15 s). The HTST method increased AA and reduced the viscosity of pasteurized milk. On the other hand, the LTLT PMi showed lower thiobarbituric acid (TBA) values, improving whiteness, specific flavor, and taste among panelists. Each level of MLE affected AA, TBA values, and viscosity during pasteruization of milk under different conditions. Nevertheless, the relationship between MLE and PM did not milk. PMi exhibited an AA range from 14.05% to 57.79%, with an average AA of 34.36% for the LTLT method and 43.13 for the HTST method. In the LTLT method, the average TBA value for PMi was 0.08 mg MDA/kg, compared to 0.15 mg MDA/kg for the HTST method. Similarly, the average fat content in PMi was slightly higher for the LTLT method (0.98 %) than for the HTST (0.95%). PMi supplemented with MLE in both pasteurization methods exhibited viscosity levels ranging from 5 to 15 mPa.s. The preference test revealed that panelists generally favored the color white of the milk. Approximately 56% of panelists stated that the aroma and taste of the milk remained strong even with the addition of the MLE, with the most preferred sensory combination being the addition of 0.2% MLE with the HTST method of matoa leaf extract to pasteurized milk can be an innovation in the dairy industry to obtain healthful, functional pasteurized milk.